Exclaustration of a religious in the light of the Canon Law 1983 and its present view in the practice of the religious Institutes - STOKŁOSA, MAREK (Prawo Kanoniczne, 2014)
Exclaustration is a particular form of lawful absence of a religious outside of his religious affiliation. In the present ecclesial legislation we come across two forms of exclaustration, namely ordinary exclaustration and imposed one. Ordinary exclaustration is granted on the request of a religious by the highest superior of the Institute with the consent of his council for the period for no longer than three years. If the religious is a cleric (deacon or priest) the permission is conditioned by the agreement of the ordinary of his future residence. Its eventual extension, after the period of three years or the granting of the indult for the period beyond three years is reserved to the Holy See in case of the religious who are members of the Institutes on the papal law and the local ordinary in case of the Institutes on the diocesan law (canon 686 §1). Granting the exclaustration for the contemplative nuns, following the papal enclosure or constitutional one (canon 667 §3) is reserved to the competence of the Holy See (canon 686 §2) in order to protect the contemplative life and its enclosure. Imposed exclaustration can be granted for important reasons for the request of the highest superior, with the consent of his council, by the Holy See in case of the religious who are members of the Institutes on the papal law and the local ordinary in case of the Institutes on the diocesan law (canon 686 §3). It is not an indult granted on the request of a religious, by the decision of the competent ecclesial authority, which obliges a religious, even against his will, to reside outside the houses of his religious Institute for essential reasons. It can be applied towards such religious, whose residence in any of the religious houses becomes burdensome or unbearable, even without their own fault (for example: mental illness). A person to whom exclaustration is applied is not denied all his/her rights and duties which are consequent to the religious profession. He/she remains incorporated to his/her Institute from which he/she can expect spiritual support, and in case of necessity, even material. According to the canon 687 he/she is only excused from such duties, which become impossible to reconcile with his/her new conditions of life (for example: consequent to the community life, everyday religious discipline or the vow of poverty). He/she remains under the supervision and care of his/her religious superiors and under the judicial authority of the local ordinary, especially if he is a clergyman. He/she has a right to wear his/her religious outfit of his/her Institute, if not decided otherwise in the indult. He is deprived both his active and passive vote.